Compensation, Work Stress, and Employee Performance: The Mediating Role of Work Motivation in Industrial Companies - Shofiyah 'Ulaa Laathi'fah; Vitradesie Noekent (Management Analysis Journal, 2024)
This study aims to determine the role of Compensation and Work Stress on Employee Performance through Work Motivation as a mediating variable. The method used is quantitative with Structural Equation Model-Partial Least Square (SEM-PLS) analysis SmartPLS version 3.0 program in data processing. The population in this study were employees of industrial companies in Central Java. The number of samples in this study were 308 employees. The results in this study indicate that compensation has a positive and significant effect on employee performance, work stress has an insignificant effect on employee performance, compensation has a positive and significant effect on work motivation, work stress has a negative and significant effect on work motivation, motivation has a positive and significant effect on employee performance, motivation can mediate the effect of compensation on employee performance, and motivation can mediate the effect of work stress on employee performance.